Low‐dimensional nanomaterial/Si heterostructure‐based photodetectors. Issue 2 (30th May 2019) - Tian, Wei; Sun, Haoxuan; Chen, Liang; Wangyang, Peihua; Chen, Xinrui; Xiong, Jie; Li, Liang
Abstract: Due to its excellent electrical and optical features, silicon (Si) is highly attractive for photodetector applications. The design and fabrication of low‐dimensional semiconductor/Si hybrid heterostructures provide a great platform for fabricating high‐performance photodetectors, thereby overcoming the inherent limitations of Si. This review focuses on state‐of‐the‐art Si heterostructure‐based photodetectors. It starts with the introduction of three different device configurations, that is, photoconductors, photodiodes, and phototransistors. Their working mechanisms and relative pros and cons are introduced, and the figures of merit of photodetectors are summarized. Then, we discuss the device physics/design, photodetection performance, and optimization strategies for Si‐based photodetectors. Finally, future challenges in the photodetector applications of Si‐based hybrid heterostructures are discussed. Abstract : The design of low‐dimensional nanomaterials integrated with Si heterostructures and their application in broadband photodetection have attracted wide research interest. The review starts with an overview of common device geometries for Si‐based photodetectors and follows it with an introduction of the remarkable progress in different kinds of heterostructures. The research challenges and opportunities of Si‐based photodetectors in the future are also provided.